CtBP Is an Essential Corepressor for BCL6 Autoregulation - Mendez, Lourdes M. (American Society for Microbiology (ASM), 2008)
The transcription repressor BCL6 plays an essential role in the formation and function of germinal centers (GCs). While normal B cells promptly shut off BCL6 when they exit the GC, many GC-derived B-cell lymphomas sustain BCL6 expression through chromosomal translocations and activating mutations. We have previously shown that a common effect of lymphoma-associated BCL6 gene alterations is to bypass a negative autoregulatory loop that controls its transcription. In this study, we report that BCL6 autoregulation is independent of several known corepressor complexes including silencing mediator for retinoid and thyroid hormone receptors, nuclear receptor coreceptor, BCL6 corepressor, and MTA3/NuRD. Furthermore, we show that BCL6 can interact with the CtBP (C-terminal binding protein) corepressor both in vitro and in vivo and that CtBP is recruited by BCL6 to its 5′ regulatory region. In lymphoma cell lines carrying BCL6 translocations, small interfering RNA-mediated CtBP knock-down selectively relieved the previously silenced wild-type BCL6 allele but not the translocated alleles, which are driven by heterologous promoters. These results demonstrate that CtBP is a novel BCL6 corepressor and suggest that a unique corepressor requirement for BCL6 autoregulation may allow GC B cells to differentially control the expression of BCL6 and other BCL6 target genes in response to environmental stimuli during the GC stage of B cell development.